Familial hidradenitis suppurativa: evidence in favour of single gene transmission. Issue 4 (August 1984) - Fitzsimmons, J S; Fitzsimmons, E M; Gilbert, G
Abstract : The three English families in this report have a total of 21 members (16 females and five males) suffering from chronic hidradenitis suppurativa. In family A the condition is associated with acne conglobata and there is vertical transmission of the disorder through three generations. In the others there is no associated cystic acne, but all those affected had a history of acne vulgaris with comedone formation, and the condition has been confirmed in two generations. It is likely that a male in an earlier generation in family B suffered from the disease and affected sibs in family C were born to different fathers. The familial aggregation and number of affected subjects suggests a single gene disorder and the pattern of transmission is consistent with autosomal dominant inheritance. Males and females are affected in successive generations and there is the anticipated variation in clinical severity in those suffering from the condition.